Modern media ethics: problems and challenges - Shevchenko, Larysa (Current issues of Ukrainian linguistics: theory and practice, 2022)
The article analyzes the ethical issues of modern media with its projection on the conceptual disposition of classical (Kantian) ethics and new ethics. The ethical component in Oswald Spengler’s concept of the history of philosophy ("The Decline of the West") is considered, in particular the thesis about shifting the center in scientific analysis from abstract and systematic to practical knowledge of the ethical nature of language and thinking. Attention is paid to non-linear views on the history of philosophy, the transformation of basic concepts in science, the "linguistic turn" in modern philosophy related to the pragmatics of natural language, which are important for understanding the evolution of ethical models of societies. Ethical dominants are considered through commensuration with human nature, in particular, its desire for freedom, the realization of aspirations in the categories of good and evil, the desire to change the world and evolve with it. Emphasis is placed on the ethical polyphony of modern societies and, at the same time, various manifestations of freedom that combine tradition and new models of world perception. Language communication, primarily in the media, whose principle of activity is based on informing and influencing, testifies to the complexity of the communicative situation. Legal criteria regarding the ethics of language communication, and cultural tradition, and real social processes in society can be as special regulations. The human evolves, society evolves, ethical values are transformed, that determine the current state and perspective of social communication.